Withdrawn_An innovative online plagiarism course for students at a South African university - Mahomed, S.; Mackraj, I.; Blewett, C. (South African Journal of Higher Education, 2023)
Plagiarism is a major concern across institutions of learning. We developed and implemented an innovative online course to teach students about plagiarism. This study aimed to ascertain why students plagiarise, and to determine whether the course would impact students’ knowledge and perceptions of plagiarism. This case study used a mixed-methods approach. The “Understanding Plagiarism” course was based on the principles of the Activated Classroom Teaching model that uses 5 digital-age pedagogies (Curation, Conversation, Correction, Creation, Chaos) to encourage engagement. Data was obtained from surveys administered before and after the course. 148 students accessed the course and 98 completed the surveys. The main reasons identified for committing acts of plagiarism included improved grades, laziness, and unintentional plagiarism. Students’ knowledge of plagiarism improved after completing the course (67% to 93%). The majority (83%) agreed that students who plagiarise should be disciplined, and 68 per cent agreed that they felt guilty if they copied from a friend, textbook, or the internet. This research shifts the discourse on plagiarism from policy to programme and in particular the implementation of active pedagogic approaches to online teaching. Two implications of this study are, firstly, active pedagogies need to be adopted to ensure effective learning, and secondly, plagiarism which is increasing should be programmatically, and not punitively addressed. Exposure to the course on plagiarism improved students’ understanding of the seriousness and the types of plagiarism.